TRADE OF LIVE BROODERS OF THE BLACK TIGER SHRIMP, PENAEUS (PENAEUS) MONODON Fabricius 1798 AT VISAKHAPATNAM, ANDHRA PRADESH - Paul, Miriam; Maheshwarudu, G.; Varma, J. B. (Journal of Indian Fisheries Association, 2015)
The demand for brooders of Penaeus monodon by the hatcheries, which are solely dependant on wild brooders for their seed production, has resulted in a vigorous fishery and trade for this species, especially along the Visakhapatnam coast. More than three hundred brooders are brought in per day for trading during the peak landing season from December to March every year. The price of gravid brooders has been declining over the years but on an average is about Rs. 30,000 per brooder. The total length of male brooders ranged from 190 to 246 mm during the three years under study and for females it varied between 210 and 330 mm. A specialized methodology for transportation, storage and trade of P. monodon brooders has been evolved over the years at Visakhapatnam Fishing Harbour. Concentrated exploitation of brooders from the wild and presence of pathogens in them makes a strong case for development of specific pathogen free brooders and conservation of wild stock. Keywords: Live brooders, black tiger shrimp, conservation, wild stock.